Martsolf's syndrome in a non-Jewish boy. Issue 4 (April 1988) - Strisciuglio, P; Costabile, M; Esposito, M; Di Maio, S
Abstract : Martsolf's syndrome has been described in Jewish people. We describe a patient of non-Jewish ancestry who has minor differences from other patients. The possible pattern of inheritance is discussed.